Porphyromonas gingivalis antibody levels and diagnosis of coronary artery disease in HIV‐positive individuals. (10th April 2017) - Berquist, V. L.; Hearps, A. C.; Ford, P.; Jaworowski, A.; Leishman, S. J.; Hoy, J. F.; Trevillyan, J. M.
Abstract : Background and Objective: Periodontal disease has been associated with cardiovascular disease in the general population. It is unknown whether IgG antibody levels for periodontal pathogens are associated with the diagnosis of coronary artery disease (CAD) in HIV‐positive individuals. Material and Methods: Twenty‐four HIV‐positive individuals (cases) with stored plasma available in the 12 months before CAD diagnosis were age‐ and sex‐matched 1:2 with 46 HIV‐positive individuals without CAD (controls). Antibody levels to whole cell extracts from periodontal pathogens Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum, as well as markers of inflammation sCD14, CXCL10 and high‐sensitivity C‐reactive protein, were compared between cases and controls using enzyme‐linked immunosorbent assays. Results: P. gingivalis ‐specific IgG levels (μg/mL) were significantly higher in individuals with CAD (median 1.48 [IQR 1.06‐2.05]) compared to controls (0.70 [IQR 0.35‐1.24], P <.001), and remained significantly higher following adjustment for traditional cardiovascular risk factors and HIV viral load (OR 21.6 [95% CI 3.73‐125.63] P= .001). There was a borderline association between A. actinomycetemcomitans IgG antibody levels (cases, median 3.86 [IQR 3.19‐4.72]; controls, 3.34 [IQR 2.59‐4.07], P =.050) and no association found between F. nucleatum antibody levels and CAD. sCD14 levels (μg/mL) were higher in cases compared with controls (median 3.45 [IQR 3.03‐4.11] vs 2.65 [IQR 2.32‐2.99] P <.001), while CXCL10 (median 127 pg/mL [IQR 88‐157] vs 153 [IQR 90‐244] P =.321) and high‐sensitivity C‐reactive protein (median 3.44 mg/L [1.98‐5.32] vs 1.85 [1.13‐6.88] P =.203) levels were not different between cases and controls. Conclusion: Periodontal bacteria may be contributing to CAD risk in HIV‐positive individuals.